Antibacterial Activity from Different Parts of Capparis spinosa L. - Firas Al-Bayati; Mohammed Al-Jarjry (College of Education for Pure Sciences, 2007)
Abstract In the present study ethanol and chloroform extracts from different parts of Capparis spinosa (flowers, fruits, leaves and roots) were screened for antibacterial activities against Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae, Pseudomonas aeruginosa and Proteus vulgaris, ethanol and chloroform extracts from C. spinosa roots showed good inhibitory effects against tested bacteria compared with standard antibiotics, meanwhile no clear activity was detected using both extracts from flowers, fruits and leaves against the test bacteria. Minimum inhibitory concentrations MIC and minimum bactericidal concentrations MBC of root extracts were determined against the tested bacteria.